Minority nations in the age of uncertainty : new paths to national emancipation and empowerment - Gagnon, Alain (University of Toronto Press, 2014)
Already translated into fifteen languages from the original French, Minority Nations in the Age of Uncertainty is an essential text on the theory of multinational federalism and the politics of minority nations.